The link between prenatal stress and indicators of fatness in children – literature review - Ewa Bryl; Tomasz Hanć (Homo, 2022)
Background: There are indications that the occurrence of metabolic diseases in children may be conditioned by factors experienced already in the utero. Aim of the study: The aim of this systematic review was to analyze the studies that examined the effects of stress experienced by a pregnant woman on the child’s adiposity rates in postnatal life. Methods: The review includes 20 articles published before March 2020 in Scopus and Medline databases with the use of following keyword combinations: /maternal or mother/, /prenatal or pregnant/, /stress or distress/ and /BMI, body mass index or overweight or obesity or body composition/. Results: The results of the research were inconsistent. Nevertheless, most articles confirmed the positive association of prenatal stress with fatness indicators in children. The review raised a question of the role of the methods applied for stress measurement (objective vs. subjective indicators) and adiposity assessment, as well as the time of prenatal exposition to stress. Conclusion: Most studies have proved that prenatal stress is related to the children adiposity in postnatal life.